Screening elite barley genotypes (Hordeum vulgare L.) for salinity tolerance and forage production under hydroponic conditions. - Chisela Kaite, Paul (Institute of Agronomy and Veterinary Hassan II, 2022)
Soil salinization presents a major problem hindering crop development in many areas of the world. Over 800 Ma are affected by soil salinity globally (Munns and Tester, 2008). This process is mainly due to various reasons ranging from the natural accumulation of soluble salts in the soil to irrigation practices. However, breeding for salinity tolerance in barley (Hordeum vulgare L.) has been productive over the past two decades with salinity levels expected to further increase from now till 2050 amid climate crisis. On one hand, selection programs such as that of ICARDA on dual-purpose barley and forage production will richly contribute to reinforcing the resilience of cereals in arid and semi-arid agricultural regions. Both sections of this study were carried out in the glasshouse and growth chamber at ICARDA, Morocco from February 2022 to August 2022. Primarily, the first set of experiments focuses on evaluating and effectively selecting from 240 elite barely genotypes (ASABYT-21 & DUAL-22) under hydroponic conditions over two screening events. With the ultimate goal of selecting high and moderately saline tolerant genotypes, 3 NaCl treatments (0mM, 100mM and 200mM) were used. The screening method adopted focused on evaluating plant response to salinity stress through 9 physiological traits (fresh root and shoot length, fresh & dry root and shoot weight, & leaf area) hence characterizing fresh and dry biomass production, biomass losses & ultimate plant survival between genotypes and across treatment trials. Observed results highlighted significant effects of salinity stress on all 9 measured traits. Over the course of the first screening events, a sheer total of top 30 genotypes were selected in extreme salinity treatments (200mM) on the basis of survival, minimal biomass loss and root & shoot biomass. With regard to salinity stress tested genotypes averaged drops of 35% and 55% in shoot biomass in 100mM & 200mM. Thereafter preselected lines plus additional 5 commercial checks were run in a confirmation experiment to validate obtained results. Of the 30 preselected lines, 23 lines confirmed the trait (salinity tolerance) in two replications. On the other hand, besides its sole use for grain yield, barley presents a rich nutritional arsenal that allows for use in feed, food and malting purposes. Hydroponic forage allows for rapid and sustainable fodder and forage production in areas restricted by climatic limitations, feed and fodder availability (off-season), integrated crop-livestock set-ups, and affordability. Over a production cycle of only 8 days, the viability of these systems is complemented with irrigation efficiency, high crop water productivity and high total fodder yielding lines. The basis of this second experiment primarily covers the development of a protocol for optimized hydroponic forage production. In light of our experimental approach, 20 CB-21 & 20 preselected lines for high biomass production from the salinity tolerance screening events were tested for hydroponic forage production in two replications. Over the course of this experiment, tested genotypes were tested across 3 irrigation applications (12, 8 & 6 ml/well/day). Ideally, green and dry fodder yields were accounted for in addition crop water productivity (CWP) for all irrigation applications. Statistical results highlighted significant differences amongst genotypes across all 3 irrigation trials. Observed results highlighted CWP of up 0.203 & 0.0208 in 12ml & 8 ml trials. With top genotypes (GIZA-126/IG:153839) able to produce 18.6 Kg/m² & 3.024 Kg/m² in green and dry fodder yield, overall fodder yield varied greatly between genotypes for all 3 trials. The basis of obtained results will serve on one hand in a validation run under salinity field conditions as compared to those obtained in hydroponics. On the other end second set of results will serve in the development of low cost (“rack or shelf”) systems for hydroponic forage production.